(untitled) (Journal of Uzbekistan’s Development and Research, 2025)
This paper explores the integration of Artificial Intelligence (AI) into English language instruction at the secondary school level, with a particular focus on its application in countries like Uzbekistan. It examines how AI technologies—such as automated essay scoring, speech recognition, chatbots, and adaptive learning platforms—can enhance various aspects of English learning, including writing, speaking, and comprehension. The study reviews specific AI tools like Grammarly, Duolingo, ELSA Speak, and Quillionz, highlighting their roles in improving personalized learning, providing instant feedback, and increasing student engagement. The paper argues that while AI is not a substitute for human teachers, it can be a powerful supplement to address key challenges in language education, such as large class sizes, limited resources, and lack of individual attention. It concludes that the thoughtful integration of AI can lead to more effective, inclusive, and future-ready English instruction, particularly in under-resourced educational settings.